2022
DOI: 10.3390/futurepharmacol2040036
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Based Drug Development for Antioxidant and Anticancer Activity

Abstract: Selenium is one of the eight necessary trace elements humans require for active health balance. It contributes in several ways to the proper functioning of selenoprotein. Selenium has received enormous interest recently due to its therapeutic potential against a number of ailments. To date, numerous chemical compounds containing selenium have been investigated for the therapy of cancer and other disorders. Unifying the selenium atom into chemical components (typically organic) greatly increased their bioactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Several human studies have demonstrated that supplementing standard-of-care chemotherapies (such as cisplatin, doxorubicin, cyclophosphamide, and busulfan) with Se (in the form of sodium selenite or organic selenium) reduces toxicity without compromising therapeutic efficacy [ 310 ]. Se-containing molecules have been investigated in various contexts: (i) tumor development and dissemination, (ii) drug delivery; (iii) multidrug resistance (MDR); and (iv) immune system modulation [ 312 , 313 ].…”
Section: Can Antioxidants Act As Pro-oxidants?mentioning
confidence: 99%
“…Several human studies have demonstrated that supplementing standard-of-care chemotherapies (such as cisplatin, doxorubicin, cyclophosphamide, and busulfan) with Se (in the form of sodium selenite or organic selenium) reduces toxicity without compromising therapeutic efficacy [ 310 ]. Se-containing molecules have been investigated in various contexts: (i) tumor development and dissemination, (ii) drug delivery; (iii) multidrug resistance (MDR); and (iv) immune system modulation [ 312 , 313 ].…”
Section: Can Antioxidants Act As Pro-oxidants?mentioning
confidence: 99%
“…A further attractive approach is the dimerization of these dyes, building molecules with two covalently linked cyanine nuclei, these chains serving as bridges between units [ 258 ]. The targeting of these compounds can also be enhanced, for example, by introducing specific antibodies to these chains [ 259 ]; Halogenation and the so-called “heavy atom effect”: The introduction of halogens and other heavy atoms, such as selenium [ 260 , 261 ], contributes above all to more efficient anticancer activity and, by increasing the lifetime of these dyes in the triplet state, to the improvement of their singlet oxygen production. The presence of iodine atoms is highlighted as the form of halogenation that most actively increases therapeutic activity [ 249 , 254 , 262 ].…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...mentioning
confidence: 99%
“…Halogenation and the so-called “heavy atom effect”: The introduction of halogens and other heavy atoms, such as selenium [ 260 , 261 ], contributes above all to more efficient anticancer activity and, by increasing the lifetime of these dyes in the triplet state, to the improvement of their singlet oxygen production. The presence of iodine atoms is highlighted as the form of halogenation that most actively increases therapeutic activity [ 249 , 254 , 262 ].…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...mentioning
confidence: 99%
“… 11 Specifically, selenium-containing compounds are of significant interest because of their antiradical/antioxidant activity, as oxidative stress plays a crucial role in the development of a number of human diseases. 12 Notably, ebselen (2-phenyl-1,2-benzoselenazol-3(2 H )-one) ( Fig. 2 ), one of the first selenium-containing compounds synthesized, 13 exhibits potent antioxidant activity and is currently under clinical investigation for treatment of a number of disorders.…”
Section: Introductionmentioning
confidence: 99%